2010
DOI: 10.1099/mic.0.041350-0
|View full text |Cite
|
Sign up to set email alerts
|

The diguanylate cyclase YddV controls production of the exopolysaccharide poly-N-acetylglucosamine (PNAG) through regulation of the PNAG biosynthetic pgaABCD operon

Abstract: In Gram-negative bacteria, production of adhesion factors and extracellular polysaccharides (EPS) is promoted by the activity of diguanylate cyclases (DGCs), a class of enzymes able to catalyse the synthesis of the signal molecule bis-(39,59)-cyclic di-guanylic acid (c-di-GMP). In this report we show that in Escherichia coli, overexpression of the YddV protein, but not of other DGCs such as AdrA and YcdT, induces the production of the EPS poly-N-acetylglucosamine (PNAG) by stimulating expression of pgaABCD, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 56 publications
0
29
0
1
Order By: Relevance
“…Two DGCs, DosC (YddV) and YdeH, are required for PAG-dependent biofilm formation. While DosC affects transcription of the PAG biosynthesis operon, pgaABCD, the activity of YdeH stabilizes the PAG biosynthesis protein PgaD posttranscriptionally (266,271). The molecular mechanism of PAG activation by c-di-GMP has recently been elucidated (271a).…”
Section: Regulation Of Biofilmsmentioning
confidence: 99%
“…Two DGCs, DosC (YddV) and YdeH, are required for PAG-dependent biofilm formation. While DosC affects transcription of the PAG biosynthesis operon, pgaABCD, the activity of YdeH stabilizes the PAG biosynthesis protein PgaD posttranscriptionally (266,271). The molecular mechanism of PAG activation by c-di-GMP has recently been elucidated (271a).…”
Section: Regulation Of Biofilmsmentioning
confidence: 99%
“…atrosepticum could be induced to flocculate through c-di-GMP-dependent production of the exopolysaccharide adhesin poly-b-1,6-N-acetyl-D-glucosamine (PNAG) (Itoh et al, 2008;Pérez-Mendoza et al, 2011b;Tagliabue et al, 2010). PNAG (and the associated flocculation phenotype) was expressed upon induction of a heterologous, constitutively active PleD, revealing that Pe.…”
Section: Introductionmentioning
confidence: 99%
“…However, the unaltered levels of bgalactosidase activity observed (with a transcriptional lacZ fusion to the pga promoter following perturbations of ppGpp or c-di-GMP levels) argue in favour of posttranscriptional regulation (Boehm et al, 2009). By contrast, Tagliabue et al (2010) have shown that c-di-GMP positively upregulates transcript levels of the E. coli pgaABCD operon. Furthermore, those authors demonstrate that PGA production does not simply respond to intracellular c-di-GMP concentration, but specifically requires the DGC activity of the YddV protein and is not affected by the overexpression of two other active DGCs, AdrA and YcdT (Tagliabue et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…By contrast, Tagliabue et al (2010) have shown that c-di-GMP positively upregulates transcript levels of the E. coli pgaABCD operon. Furthermore, those authors demonstrate that PGA production does not simply respond to intracellular c-di-GMP concentration, but specifically requires the DGC activity of the YddV protein and is not affected by the overexpression of two other active DGCs, AdrA and YcdT (Tagliabue et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation